Capacity Building for Fish Farmers in Linggang Tering Seberang Village in Independent Fish Feed Production and Fish Disease Control: Peningkatan Kapasitas Petani Budidaya Ikan di Kampung Linggang Tering Seberang dalam Pembuatan Pakan Ikan Mandiri dan Pengendalian Penyakit Ikan - Susanto, Adi; Agustina, Agustina; Anshorullah, Muhammad Auzan; Astri, Andi; Putri, Riska Amalia; Sart, Theresi Reselyn Amabilis; Meiliasari, Aninda Dewi; Ariani, Sinta; Kurniawan, Andre; Agusmanto, Anditia; Adi, Davina Mutiara; Fadhila, Andini; Antoni, Djaman Fredereik Julian (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Kampung Linggang Tering Seberang has significant aquaculture potential and plays an important role in providing nutrition from fish, especially in the Tering District. Constraints related to fish feed and diseases have caused this business to not develop well. Improving understanding related to fish farming activities, especially the independent provision of fish feed and disease control, is important so that interest in fish farming continues to grow. This training was conducted at the Village Hall of Kampung Lenggang Tering Seberang, with a total of 20 participants from the Pokdakan in the vicinity of Kampung Lenggang Tering Seberang. The training activities are conducted with the delivery of theory and practice. The training results show that the interest of fish farmers has increased in understanding the process of making fish feed with simple formulations and the production of fish probiotics. This is evident from the enthusiasm of the fish farmers during the Q&A session and the high level of engagement in the practical activities. The participants' understanding of the function of fish feed increased from 15% to 85%, while the understanding of the function of feed for growth increased from 45% to 75%, for disease prevention from 45% to 65%, and for fish health from 10% to 50%. The participants' understanding of the good feed content, which should include protein, fat, and carbohydrates, increased from 30% to 75%. Meanwhile, the participants' response before the training regarding the selection of feed raw materials showed that 60% chose bran flour, but after the training, the participants' response shifted to fish meal with a percentage reaching 75%.